2012
DOI: 10.1002/hbm.22019
|View full text |Cite
|
Sign up to set email alerts
|

Seeking huntington disease biomarkers by multimodal, cross‐sectional basal ganglia imaging

Abstract: Neurodegeneration of the striatum in Huntington disease (HD) is characterized by loss of medium-spiny neurons, huntingtin nuclear inclusions, reactive gliosis, and iron accumulation. Neuroimaging allows in vivo detection of the macro- and micro-structural changes that occur from presymptomatic stages of the disease (preHD). The aim of our study was to evaluate the reliability of multimodal imaging as an in vivo biomarker of vulnerability and development of the disease and to characterize macro- and micro-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 59 publications
10
59
3
Order By: Relevance
“…Evaluation of iron content in controls, as reflected in susceptibility values against reported iron content measured through biochemical techniques and QSM in previous studies,16 17 20 34 35 revealed excellent linear approximations: coefficient of determination (R 2 ) >0.90 (see online supplementary table S2 and supplementary figure S1A,B). Iron content in the HD groups, as previously estimated through relaxometry,7 MFC9 and FDRI,3 similarly exhibited good to excellent linear approximations with the iron content in the present study (pre-HD R 2 =0.77 and 0.80; symp-HD R 2 =0.80–0.97) (see online supplementary table S2 and supplementary figure S1C,D). We also found statistically significant positive correlations between susceptibility values and disease burden scores in all HD participants (pre-HD and symp-HD together) in the putamen (r=0.39, p<0.001) and caudate (r=0.32, p<0.01) (see figure 3).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Evaluation of iron content in controls, as reflected in susceptibility values against reported iron content measured through biochemical techniques and QSM in previous studies,16 17 20 34 35 revealed excellent linear approximations: coefficient of determination (R 2 ) >0.90 (see online supplementary table S2 and supplementary figure S1A,B). Iron content in the HD groups, as previously estimated through relaxometry,7 MFC9 and FDRI,3 similarly exhibited good to excellent linear approximations with the iron content in the present study (pre-HD R 2 =0.77 and 0.80; symp-HD R 2 =0.80–0.97) (see online supplementary table S2 and supplementary figure S1C,D). We also found statistically significant positive correlations between susceptibility values and disease burden scores in all HD participants (pre-HD and symp-HD together) in the putamen (r=0.39, p<0.001) and caudate (r=0.32, p<0.01) (see figure 3).…”
Section: Resultssupporting
confidence: 85%
“…However, the susceptibility values reported for controls were within the range of variation previously reported in other QSM studies,16 17 35 38 reflected the same rank ordering by brain structure (from highest to lowest: pallidum, putamen, caudate and thalamus) and obtained good to excellent linear approximation not only with measures from other QSM16 17 35 40 but also biochemical studies 20 34. This was also the case for pre-HD and symp-HD groups, with reference to iron content measured with MRI techniques other than QSM 3 7 9. Further studies that employ dual-echo acquisition of GRE data are, however, required to further validate the present findings.…”
Section: Discussionsupporting
confidence: 79%
“…Similar higher sensitivity of susceptibility compared to R2* has been observed previously in detecting tissue changes in multiple sclerosis, in which demyelination is a known disease hallmark 46 . In addition, some striatal demyelination and loss of tissue integrity in premanifest-HD might also partly explain the increased mean diffusivity observed in another study 19 . It is worth noticing that in most of the deep gray matter regions investigated in this study, myelin content is not expected to be very high, therefore iron change is still likely to be the dominant source of the observed susceptibility and R2* increases in premanifest-HD group.…”
Section: Discussionmentioning
confidence: 87%
“…These studies in advanced HD have sparked interest in investigating potentially abnormal iron accumulation during earlier stages of the disease. Several recent studies using R2* measurements 18, 19 or magnetic susceptibility-related measures, such as phase 20 , Magnetic Field Correlation 21 and field shift 17 , have indeed suggested that brain iron levels are increased in premanifest or early stage HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Huntington disease (HD) 26 and dentatorubral-pallidoluysian atrophy (DRPLA) 27 are both late clinical onset, polyglutamine repeat disorders inherited in an autosomal dominant way and selectively causing atrophy of the CN in HD and the GP in DRPLA. In both disorders an anticipation phenomenon occurs meaning that the next generation of gene carriers will have a longer polyglutamine repeat region and will present clinical symptoms earlier in life.…”
Section: Discussionmentioning
confidence: 99%